THE EFFECT OF USING AUDIO-VISUAL MEDIA ON THE ABILITY TO WRITE SHORT STORIES - Agus Sulaeman; Koh Young Hun (STIBA IEC JAKARTA, 2022)
This study aims to determine the effect of using audio visual media on the ability to write short stories for seventh grade students of SMP Muhammadiyah 1 Tangerang City. The method used is a quasi-experimental experimental method using two classes, namely the experimental class which is given treatment in the form of audio visual media and the control class which is treated with audiovisual media. not given treatment as a comparison class. The data collection technique uses a short story writing essay test and a questionnaire to determine student responses to audio-visual mediaFrom the pretest data, students in the control class obtained an average score of 52.1 with a variance of 52.04, while the average score of students in the experimental class obtained an average score of 52.3 with a variance of 53.96. Then H0 is accepted because tcount = 0.1069 < 2.0021 = ttable, it can be stated that there is no difference in giving the pretest to the control class and the experimental class. From the posttest data of students in the control class using conventional learning, an average score of 59.8 with a variance of 86.89 was obtained, while the average score of students in the experimental class using audio-visual media obtained an average score of 74.2 with a variance of 103, 22. Then HI is accepted because tcount = 5.7491 > 2.0021 = ttable, it can be stated that giving posttest to the control class that uses conventional learning and the experimental class that uses audio-visual media, there are differences from the results of this research, it can be concluded that there is an effect of using audio-visual media on the ability to write short stories for seventh grade students of SMP Muhammadiyah 1 Tangerang City